2016
DOI: 10.1063/1.4972555
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of device structures for the dielectric breakdown measurement of hexagonal boron nitride

Abstract: Improving the film quality in the synthesis of large-area hexagonal boron nitride films (h-BN) for two-dimensional material devices remains a great challenge. The measurement of electrical breakdown dielectric strength (EBD) is one of the most important methods to elucidate the insulating quality of h-BN. In this work, the EBD of high quality exfoliated singlecrystal h-BN was investigated using three different electrode structures under different environmental conditions to determine the ideal electrode struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…Note that this value is higher than those previously reported for TiO 2 (≈3 MV cm −1 ) [25] and mechanically exfoliated h-BN (≈12.0 MV cm −1 ) via CAFM. [26][27][28] Additional discussion about the calculation and meaning of dielectric strength can be found in Note S3 (Supporting Information). This observation further indicates the extraordinary potential of ultrathin CaF 2 films to serve as dielectric in nanoelectronic devices.…”
Section: Doi: 101002/adma202002525mentioning
confidence: 99%
“…Note that this value is higher than those previously reported for TiO 2 (≈3 MV cm −1 ) [25] and mechanically exfoliated h-BN (≈12.0 MV cm −1 ) via CAFM. [26][27][28] Additional discussion about the calculation and meaning of dielectric strength can be found in Note S3 (Supporting Information). This observation further indicates the extraordinary potential of ultrathin CaF 2 films to serve as dielectric in nanoelectronic devices.…”
Section: Doi: 101002/adma202002525mentioning
confidence: 99%
“…25 The structural damage is due to the release of enormous amounts of energy at the instant of breakdown. The catastrophic HBD failure in very thick h-BN (20−30 nm), as used by Hattori et al, 58 is qualitatively similar to the structural damages suffered by capacitors in the early generations of CMOS technology when physically thicker (typically 10−100 nm) gate dielectrics were used. 59 A novel finding is that partial removal of h-BN material can still be observed even for breakdown at PBD hardness (I comp < 100 nA) and for considerably thinner (2−5 nm) h-BN films as compared to those reported by Hattori et al 25 What is notable is that some pitting is observed in h-BN even under very low current compliance in PBD (I comp = 1−5 nA), in sharp contrast to measurements on conventional SiO 2 60,61 and HfO 2 62 gate dielectrics.…”
Section: Nano-spectroscopy Of Defects Using Lowmentioning
confidence: 72%
“…7 Furthermore, h-BN is an insulator with a bandgap 8 of ∼6 eV, and thus one can use h-BN as a gate dielectric material and seamlessly integrate with a wide range of 2D semiconductors to create 2D heterostructure electronic devices, such as transistors 9 and resistive switching memories. 10 The utility of h-BN as a gate dielectric is shown by the measurement of the tunneling current 11−13 and breakdown field strength 14,15 in both chemical vapor deposited polycrystalline h-BN and high-pressure/high-temperature singlecrystal h-BN. Notable here are the pioneering works of Hattori et al showing that (a) dielectric breakdown field strength in single-crystal h-BN is higher along out-of-plane directions compared to in-plane directions 15 and (b) physical removal of h-BN occurs at the breakdown spot under hard breakdown conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The utility of h-BN as a gate dielectric is shown by the measurement of the tunneling current and breakdown field strength , in both chemical vapor deposited polycrystalline h-BN and high-pressure/high-temperature single-crystal h-BN. Notable here are the pioneering works of Hattori et al showing that (a) dielectric breakdown field strength in single-crystal h-BN is higher along out-of-plane directions compared to in-plane directions and (b) physical removal of h-BN occurs at the breakdown spot under hard breakdown conditions .…”
Section: Introductionmentioning
confidence: 99%